The CFS international capital flow database: A user's guide - Christian J. Offermanns; Marcus Pramor (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
This paper documents the methodology underlying the construction of a global database of gross foreign asset and liability positions for 153 countries over the period 1970 to 2004 and illustrates some key data characteristics. The data cover both inflows and outflows of capital and thus allow for an assessment of the degree of international financial integration. In addition to net foreign asset stocks, we also provide details on the composition of the main asset and liability categories, namely the foreign direct investment, equity investment and debt components. Finally, we report on valuation changes as one of the main sources of discrepancy between transaction-based capital flow data and stock values of investment positions. The dataset is available for download at www.ifk-cfs.de/fileadmin/downloads/data/cfs-icfd.zip.
urn:nbn:de:hebis:30-48557
Keywords: F21; F34; F32; 330; Net Foreign Assets; Valuation Adjustment; International Financial Integration; Auslandsvermögen; Auslandsverschuldung; Direktinvestition; Portfolio-Investition; Internationale Kapitalmobilität; Statistische Datenbank; Welt